Maternal behavior is impaired by methamphetamine administered during pre-mating, gestation and lactation - Slamberová, Romana; Charousová, Petra; Pometlová, Marie (Reproductive toxicology (Elmsford, N.Y.), 2005)
Previous studies demonstrated that stimulant drugs, such as cocaine or amphetamine, administered during gestation or lactation may attenuate maternal behavior in rats. The effect of methamphetamine (MA), a drug whose usage has increased lately, on maternal behavior has not yet been investigated. The present study tested the effect of MA (5 mg/kg daily) administered prior to, during and after gestation on maternal behavior. Regularity of the estrous cycle, the incidence of impregnation, and the weight gain was compared between groups (control, saline- and MA-treated). Maternal behavior was examined using two tests: Observation test (without disturbance of the mother and pups) and Retrieval test (with short separation of pups from the mother). All tests were conducted prior to dosing each day. In the Observation test, MA decreased the blanket position of active nursing, while increasing passive nursing. There were no MA-induced changes in other maternal activities such as mother being in the nest, in contact with pups, or grooming pups. MA increased some non-maternal activities, such as drinking, eating, and sleeping, while decreasing stereotypic behavior (sniffing and rearing) when compared to controls. In the Retrieval test, MA-treated mothers were slower in retrieving the first pup, returning the first pup into the nest, and returning all pups into the nest. Interestingly, there were differences in maternal behavior also in saline-treated mothers relative to controls. Saline-treated mothers spent more time in the nest and groomed pups more than controls or MA-treated mothers. In conclusion, the present study demonstrates a novel finding that MA administered during pre-mating, gestational and lactational periods has a negative effect on maternal behavior toward pups.
Keywords: Pregnancy; Sexual Behavior, Animal; Female; fertilita; krysa rodu Rattus; zvířata; stimulanty centrálního nervového systému; mateřské chování; hmotnostní přírůstek; potkani Wistar; methamfetamin; Estrous Cycle; těhotenství u zvířat; ženské pohlaví; Rats, Wistar; laktace; Male; Fertility; Maternal Behavior; těhotenství; Weight Gain; estrální cyklus; Rats; Pregnancy, Animal; Animals; Central Nervous System Stimulants; mužské pohlaví; sexuální chování zvířat; Lactation; Methamphetamine